EFFECT OF VARIOUS MEASURES ON POWER ADSORPTION ION KROMIUM (III) AND COLOMUM (VI) IN LAND DIATOMAE - Susila Kristianingrum; Siti Sulastri (Jurnal Penelitian Saintek, 2008)
This research was done in Chemistry Laboratory FMIPA UNY. The aim of this research is to know the effect of diatomaeous earth soaking in a such acid on its adsorption power for heavy metal chromium(III) and chromium(VI) ions.The subject of this research is the diatomaeous earth from Sangiran Village, Sragen, Jawa Tengah. The object of this research is the diatomaeous earth properties soaking in such acid. Independent variables of this research are acid type, acid soaker concentration and the type of metal ion adsorbed. Dependent variable is its adsorption power for heavy metal chromium(III) and chromium(VI) ions. Experiment procedure consists of some steps: preparation, the diatomaeous earth treatment on chloride acid, nitric acid, and sulphuric acid, properties of the diatomaeous earth adsorbent for chromium(III) and chromium(VI) investigation. FTIR analyzing on original and treated diatomaeous earth and AAS analyzing to determine chromium(III) and chromium(VI) concentration before and after being diatomaeous earth soaker.The conclusion from this research was the diatomaeous earth soaking on such acids can caused adsorption power differences. Optimum adsorption power for chromium(III) occurred on a half concentrate chloride acid soaking (18.50%), concentrate nitric acid (65%), and concentrate sulphuric acid ((96%). Optimum adsorption power for chromium(VI) occurred on a half concentrate chloride acid soaking (18.50%), half concentrate nitric acid (32.50%), and an eight concentrate sulphuric acid (12%). Both original and treated diatomaeous earth has a similar FTIR spectrum pattern.